Hamimaera hamigera Haswell 1879 - Hughes, Lauren E. (Zenodo, 2016)
Hamimaera hamigera (Haswell, 1879b) Moera hamigera Haswell, 1879b: 333, pl. 21, fig. 1. Maera hamigera .— Stebbing, 1888: 1790.— Della Valle, 1893: 723.— Stebbing 1906: 437.— Barnard & Barnard, 1983: 623.—? Ren, 2012: 240 –242, fig. 104. Linguimaera hamigera .— Lowry & Springthorpe, 2005: 249 –252, figs. 11–13. Hamimaera hamigera .— Krapp-Schickel, 2008: 29 –30, fig. 27. not Maera hamigera .— Walker 1909: 335, pl. 43, fig. 5, pl. 3.— Karaman & Ruffo, 1971: 152, figs 21–23.— Lyons & Myers, 1993: 587, fig. 10. (= L. caesaris Krapp-Schickel, 2003) not Maera hamigera .— Stebbing 1910a: 600.— K.H. Barnard, 1916: 196, pl. 27, figs 11–12.— Chilton, 1921: 73.— J.L. Barnard, 1965: 507, fig. 16 (in part).— Ledoyer, 1983: 523, figs 196–197.— Karaman, 1982: 312, fig. 211.— Myers, 1997: 109.— Appadoo, Myers & Fagoonee, 2002: 664 –668, figs 14–16. Material examined. New South Wales: 2 specimens, AM P.77036, Surgeons Reef, north of North West Solitary Island (30°00′27″S 153°16′13″E), 10–11 m, orange sponge, 30 April 2005, coll. P.B. Berents (NSW 2790); 3 specimens, AM P.77035, Chopper Rock, northwest of North West Solitary Island (30°00′30″S 153°15′22″E), 17 m, ascidian Herdmania momus , 29 April 2005, coll. S.J. Keable (NSW 2778); 3 specimens, AM P.77009, Black Rocks, south of Smoky Cape (30°56′59″S 153°04′29″E), 10.3 m, reef rock encrusted with red and green algal turf, 10 February 2002, coll. S.J. Keable (NSW 1814); 6 specimens, AM P.77012, Black Rock, south of Smoky Cape (30°56′58″S 153°04′32″E), 10 m, reef rock, 13 February 2002, coll. S.J. Keable (NSW 1867); 1 specimen, AM P.77021, north west corner of Green Island, north of Smoky Cape (30°54′41″S 153°05′18″E), 8–10 m, ascidians covered with algae and encrustations, 15 February 2002, coll. R.T. Springthorpe (NSW 1923); 2 specimens, AM P.77016, northwest corner of Green Island, north of Smoky Cape (30°54′41″S 153°05′18″E), 11 m, tunicates and sponge, 15 February 2002, coll. S.J. Keable (NSW 1914); 2 juvenile specimens, AM P.97858, north west corner of Green Island, north of Smoky Cape (30°54′40″S 153°5′18″E) 7.3m, airlift, 15 February 2002, coll. Kate Attwood (NSW 1921); 6 specimens, AM P.77074, southwest side of Boondelbah Island, east of Port Stephens (32°42′30″S 152°13′32″E), 20 m, under stones, 10 March 2006, coll. R.T. Springthorpe (NSW 2914); 3 specimens, AM P.77082, northeast side of Little Broughton Island, northeast of Port Stephens (32°37′05″S 152°20′06″E), 17 m, rock reef with gutters and sand patches, macroalga Ecklonia sp. holdfasts, 11 March 2006, coll. R.T. Springthorpe (NSW 2940); 1 specimen, AM P.77101, sewage pipeline, Nelson Bay, Port Stephens (32°43′11″S 152°08′28″E), 10 m, hydroids on rubble, 15 March 2006, coll. K.B. Attwood (NSW 3052); 3 specimens, AM P.36639, Twofold Bay, Quarantine Bay (37°04′42″S 149°53′E), 2 m, seagrass Posidonia sp., airlift, 9 October 1984, coll. S.J. Keable and J.T. van der Velde (Q6, Q8); 19 specimens, AM P.77029, Diamond Reef, south-east of Hallidays Point (32°05′26″S 152°33′05″E), 17 m, brown-green sponge, 21 March 2003, coll. P.B. Berents, S.J. Keable and R.T. Johnson (NSW 2243); 11 specimens, AM P.77031, east of Red Head (32°03′17″S 152°33′14″E), 12.4 m, orange lacy bryozoan, 22 March 2003, coll. AM party (NSW 2245); 2 specimens, AM P.77033, east of Red Head (32°03′17″S 152°33′14″E), 9.5 m, brown convoluted sponge, 22 March 2003, coll. P.B. Berents, S.J. Keable and R.T. Johnson (NSW 2260); 1 male specimen, AM P.97859, Bare Island, Botany Bay (33°59′S 151°13′E), 3–7 m, macroalga Ecklonia radiata kelp holdfast, 18 March 2011, coll. K.B. Attwood and L.E. Hughes (MI NSW 4014); 1 male specimen, AM P.77626, south of Baronda Head, north of Tathra (36°41′12″S 149°59′53″E), 12 m, on yellow sponge, 5 April 2008, coll. R.T. Springthorpe (MI NSW 3275). Type locality. Port Jackson, New South Wales, Australia (33°51′S 151°16′E). Distribution. New South Wales: Smoky Cape; Coffs Harbour; Solitary Islands; Port Stephens; Hallidays Point; Red Head; Port Jackson Wattamolla; Munganno Point; Bare Island; Twofold Bay; Tathra (Haswell 1879; Lowry & Springthorpe 2005; current study). Tasmania: eastern slope of Bass Strait (Lowry & Springthorpe 2005). : Published as part of Hughes, Lauren E., 2016, New genera, species and records of Maeridae from Australian Waters: Austromaera, Ceradocus, Glossomaera, Hamimaera, Huonella gen. nov., Linguimaera and Maeraceterus gen. nov. (Crustacea: Amphipoda), pp. 1-81 in Zootaxa 4115 (1) on pages 32-33, DOI: 10.11646/zootaxa.4115.1.1, http://zenodo.org/record/255539 : {"references": ["Haswell, W. A. (1879 b) On some additional new genera and species of amphipodous crustaceans. Proceedings of the Linnean Society of New South Wales, 4 (4), 319 - 350, pls. 318 - 324. http: // dx. doi. org / 10.5962 / bhl. part. 22854", "Stebbing, T. R. R. (1888) Report on the Amphipoda collected by H. M. S. Challenger during the years 1873 - 1876. Report on the Scientific Results of the Voyage of H. M. S. Challenger during the years 1873 - 76, Zoology, 29, 1 - 1737, pls. 1731 - 1210.", "Della Valle, A. (1893) Gammarini del Golfo di Napoli. Fauna und Flora des Golfes von Neapel, 20, 1 - 948, pls. 941 - 961.", "Stebbing, T. R. R. (1906) Amphipoda. I. Gammaridea. Das Tierreich, 21, 1 - 806.", "Barnard, J. L. & Barnard, C. M. (1983) Eds. Freshwater Amphipoda of the World. Vol. I. Evolutionary Patterns. Vol. II. Handbook and Bibliography. Mount Vernon, Virginia, Hayfield Associates.", "Ren, X. (2012) Crustacea Amphipoda Gammaridea (II). Fauna Sinica Invertebrata, 43, pp. 651. [ISBN 978 - 7 - 03 - 033327 - 8]", "Lowry, J. K. & Springthorpe, R. T. (2005) New and little-known melitid amphipods from Australian waters (Crustacea: Amphipoda: Melitidae). Records of the Australian Museum, 57 (2), 237 - 302. http: // dx. doi. org / 10.3853 / j. 0067 - 1975.57.2005.1463", "Krapp-Schickel, T. (2008) What has happened with the Maera - clade (Crustacea, Amphipoda) during the last decades? Bolletino del Museo Civico di Storia Naturale di Verona, 32, 3 - 32.", "Walker, A. O. (1909) Amphipoda Gammaridea from the Indian Ocean, British East Africa, and the Red Sea. Transactions of the Linnean Society, London, Series 2, Zoology, 12 (4), 323 - 344, pls. 342 - 343.", "Karaman, G. S. & Ruffo, S. (1971) Contributo alla conoscenza delle specie mediterranee del genere Maera. Memorie del Museo Civico di Storia Naturale, Verona, 19, 113 - 176.", "Lyons, J. & Myers, A. A. (1993) Amphipoda Gammaridea from coral rubble in the Gulf of Aqaba, Red Sea: families Megaluropidae, Melitidae, Phliantidae, Phoxocephalidae, and Urothoidae. Journal of Natural History, 27 (3), 575 - 598. http: // dx. doi. org / 10.1080 / 00222939300770331", "Krapp-Schickel, T. (2003) Linguimaera Pirlot, 1936 (Crustacea, Amphipoda, Melitidae), a valid genus. Memoirs of Museum Victoria, 60 (2), 257 - 283.", "Stebbing, T. R. R. (1910 a) Scientific results of the trawling expedition of H. M. C. S. \" Thetis \". Crustacea. Part V. Amphipoda. Australian Museum Memoir, 4, 565 - 658, pls. 547 - 560.", "Barnard, K. H. (1916) Contributions to the crustacean fauna of South Africa. 5. - The Amphipoda. Annals of the South African Museum, 15, 105 - 302, pls. 126 - 128. http: // dx. doi. org / 10.5962 / bhl. title. 10646", "Chilton, C. (1921) Report on the Amphipoda obtained by the F. I. S. \" Endeavour \" in Australian seas. Biological Results of the Fishing Experiments carried on by the F. I. S. \" Endeavour \", 1909 - 14, 5 (2), 33 - 92.", "Barnard, J. L. (1965) Marine Amphipoda of atolls in Micronesia. Proceedings of the United States National Museum, 117, 459 - 551. http: // dx. doi. org / 10.5479 / si. 00963801.117 - 3516.459", "Ledoyer, M. (1983) Crustaces amphipodes gammariens. Familles des Acanthonotozomatidae a Gammaridae. Faune de Madagascar, 59 (1), 1 - 598.", "Karaman, G. S. (1982) Family Gammaridae. Memoires de l'Institute Oceanographique, Monaco, 13, 245 - 364.", "Myers, A. A. (1997) Amphipoda from the South Pacific: Western Samoa. Records of the Australian Museum, 49, 99 - 109. http: // dx. doi. org / 10.3853 / j. 0067 - 1975.49.1997.1260", "Appadoo, C., Myers, A. A. & Fagoonee, I. (2002) The genera Quadrimaera and Maera (Amphipoda: Gammaridea: Melitidae) from Mauritius. Journal of Natural History, 36 (6), 641 - 673. http: // dx. doi. org / 10.1080 / 00222930010025518"]}